Characterisation of the AT4G11100 gene, a negative regulator of disease resistance in Arabidopsis thaliana - McCrindle, Tyronne K (Department of Molecular and Cell Biology, 2015)
Plants have evolved a complex system of defence to prevent pathogen establishment. The Arabidopsis thaliana cir1 (constitutively induced resistance 1) mutant displays enhanced resistance to infection by the virulent bacterial pathogen Pseudomonas syringae and constitutively expresses a number of defence genes. Evidence suggests that CIR1 is a negative regulator of plant immunity important in the absence of pathogen attack. Genetic mapping experiments indicate that cir1 is located on the lower arm of chromosome 4 of A. thaliana and may be one of 8 known genes in the region. Analysis of T-DNA knockouts of these 8 genes suggests that AT4G11100 is the mostly likely candidate for CIR1. This project established that the disease resistance phenotype of cir1 is temperature dependent and linked to reduced plant growth. Genetic crosses between cir1 and at4g11100 T-DNA knockout mutants revealed that the mutants complement and therefore AT4G11100 is not CIR1. However, like cir1, the at4g11100 T-DNA knockout mutants display enhanced disease resistance. Over expression of AT4G11100 leads to increased susceptibility to infection by Pseudomonas syringae (Pst) and reduced induction of the salicylic acid defence gene PR2 following Pst infection, suggesting that AT4G11100 may too be a negative regulator of immunity. Additionally, a plant line with exceptionally high AT4G11100 expression levels displayed distinct leaf morphology, possibly implicating AT4G11100 in leaf development.